On the nucleation of GaP/GaAs and the effect of buried stress fields - Zelcovit, J. G.; Bortoleto, J. R R [UNESP]; Bettini, J.; Cotta, M. A. (Springer Nature, 2006)
We have recently shown that spatial ordering for epitaxially grown InP dots can be obtained using the periodic stress field of compositional modulation on the InGaP buffer layer. The aim of this present work is to study the growth of films of GaP by Chemical Beam Epitaxy (CBE), with in-situ monitoring by Reflection High Energy Electron Diffraction (RHEED), on layers of unstressed and stressed GaAs. Complementary, we have studied the role of a buried InP dot array on GaP nucleation in order to obtain three-dimensional structures. In both cases, the topographical characteristics of the samples were investigated by Atomic Force Microscopy (AFM) in non-contact mode. Thus vertically-coupled quantum dots of different materials have been obtained keeping the in-place spatial ordering originated from the composition modulation. © 2006 Materials Research Society.
Keywords: Chemical beam epitaxy; Epitaxial growth; Nucleation; Reflection high energy electron diffraction; Semiconductor quantum dots; Stress analysis; Surface topography; Compositional modulation; In-situ monitoring; Periodic stress; Vertically-coupled quantum dots; Semiconducting gallium arsenide